Structural Studies and Spectroscopic properties of Quinolizidine Alkaloids (+) and (-)-Lupinine in different media - Ruiz Hidalgo, José (2019)
The quinolizidine alkaloids, as numerous species of lupine (Lupinus spp.), are toxic andhave biological effect on the nervous system. Hence, four (+) and (-)- molecular structuresof quinolizidine alkaloid lupinine, named C0, C1a, C1b and C1c have been theoreticallydetermined in gas phase and in aqueous solution by using hybrid B3LYP/6-31G*calculations. The studied properties have evidenced that the most stable C1c form presentthe higher populations in both media while the predicted infrared, Raman, 1H-NMR and 13C-NMR and ultra-visible spectra suggest that probably other forms in lower proportioncould be also present in water, chloroform and benzene solutions, as evidenced by the lowRMSD values observed in the 1H- and 13C-NMR chemical shifts. The C1c form presentsthe lower corrected solvation energy in water while the NBO and AIM studies suggest forthis form a high stability in both media. In addition, the predicted ECD spectra of all (+)and (-)-lupinine forms in methanol solution evidence clearly that the C1b forms is presentin the solution because its spectrum presents a negative Cotton effect as observed in the experimental one.